Integrated common core curriculum: environmental education through landscape architecture - Swihart, Emily (Kansas State University, 2014)
Recent development and adoption of Common Core State Standards has shifted academic emphasis within public and accredited schools. Consistent, national educational goals have standardized education and have resulted in a challenge to educators to assist all students in achieving maximum test scores. The curricular subjects of math, science, and literacy are the primary emphasis of instruction and achievement. Standardized testing is the dominant means to determine whether students are reaching acceptable achievement. “Integrated Common Core Curriculum: Environmental Education Through Landscape Architecture” explores the potential of incorporating basic landscape architectural knowledge into a fourth-grade curriculum while striving to achieve learning standards as determined by the Common Core and the Iowa Core Curriculum. Exploring the application of current educational criteria, the researcher developed an educational unit that utilizes the process of park design as a simplified version of a landscape architect’s approach in order to emphasize math, literature, science, creative thinking, and teamwork. Implementing environmental education through place-based education theory enhances unit strength by providing enhanced emotional, mental, and physical health benefits to children. Created during this study, an instructional unit was evaluated by a convenience sample of educators. Through the use of an open-ended questionnaire, preliminary review results indicate a strong potential for the unit to successfully demonstrate the basic process of landscape architecture design through the use of the local place simultaneously achieving academic standards. Review results identify a variety of limitations and challenges the unit would encounter for implementation including a current subject focused instructional philosophy within the school district verse the thematic focus of the unit. Additionally, ever-evolving standards would require regular unit updates, although school districts face perennial budget challenges and educators are limited on time. As a student of landscape architecture, I recognize that the profession offers a unique opportunity to model place-based, multi-subject practices realized in the practice of landscape architecture. Promoting the profession of landscape architecture through a curricular unit provides an environmental education tool and provides the opportunity for students to explore a career option within the classroom setting.
Keywords: Common core; Landscape architecture; Place-based education; Park design; Elementary curriculum; Elementary Education (0524); Landscape Architecture (0390)